Pengembangan Plastik Pengemas Obat yang Informatif dan Beradsorben - Eling Bunga Nurani; Amatullah Syarifah; Nilta Dizzania; Deni Agustin Wulandari; Amyda Ayu Dianritami (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
The problem of labeling on plastic medicine packaging which is less informative and its function in maintaining drug quality is very crucial. The purpose of this research and development is to produce informative and absorbent drug packaging plastics. The method used is the ADDIE research and development model. The development stage is carried out by testing physical stability and chemical stability testing. The implementation phase was carried out by asking for responses from 10 pharmacists and 15 ordinary people. Based on the results of the physical stability test, the drug stored in the plastic packaging of the drug that was developed was more physically stable. Based on the results of chemical stability tests, the absorbance of drugs stored in drug packaging plastics developed is more stable than ordinary drug packaging plastics, which is indicated by a smaller slope value. Based on the questionnaires distributed to pharmacists, they strongly agree with the adequacy of the information and agree with the readability, attractiveness of appearance, and usefulness of the adsorbent in the plastic drug packaging developed. Based on the questionnaires distributed to the general public, they strongly agree with the adequacy of the information and agree with the readability, attractiveness of appearance, and the usefulness of the adsorbent in the plastic drug packaging developed.